Local Awareness and Interpretations of Species Extinction in a Rural Chinese Biodiversity Hotspot - Ma, Heidi; Papworth, Sarah K.; Ge, Tianbei; Wu, Xiaohan; Yu, Chuyue; Zhang, Hanxue; Turvey, Samuel T. (Frontiers in Conservation Science, 2021)
Incorporating local perspectives is fundamental to evidence-based conservation, for both understanding complex socio-ecological systems and implementing appropriate management interventions. How local communities understand extinction, and whether these views affect perceptions of biodiversity loss and the effect of anthropogenic activities, has rarely been evaluated explicitly in conservation projects. To target this data gap, we conducted 185 interviews to assess levels and patterns of understanding about wildlife decline and extinction in rural communities around Bawangling National Nature Reserve, Hainan, China, a priority conservation site that has experienced recent species losses. Interviewees showed varying awareness of declines and extirpation of local wildlife species. Two-thirds did not consider the permanent disappearance of wildlife to be possible; among those who did, only one-third could comprehend the scientific term ‘extinction’. Thinking extinction is possible was associated with identifying declined and extirpated species, but not with perceiving locally-driven human activities, such as hunting, as the reason for wildlife loss. The government was seen as the entity most responsible for conservation. Variation found around local perceptions of extinction, its drivers, and conservation responsibility demonstrates that comprehension of key conservation concepts should not be assumed to be homogenous, highlighting the challenge of transposing scientific concepts between different social and cultural settings. Proactively incorporating local perspectives and worldviews, especially by obtaining context-specific baseline understandings, has major implications for other contexts worldwide and should inform conservation planning and management.